The effect of microwave power, extraction time and solvent ratio of microwave assisted extraction (MAE) method on the yield of pectin from Nephelium lappaceum - Talitha Ayu Daffa Athallah; Muhammad Alfid Kurnianto; Anugerah Dany Priyanto; Hadi Munarko; Andre Yusuf Tisna Putra; Luqman Agung Wicaksono (Konversi, 2025)
Pectin is a complex polysaccharide that is widely used in the food, pharmaceutical, and cosmetic industries as a thickening agent, stabilizer, and emulsifier. Extraction methods such as hot acid extraction have limitations in terms of time efficiency and yield. Therefore, the Microwave-Assisted Extraction (MAE) method is a faster and more efficient alternative. Microwave-assisted extraction is a potential method for pectin extraction from rambutan binjai peel. Conventional extraction methods (direct heating) are widely used, but have drawbacks such as long process time, low yield, and the risk of pectin degradation. Environmentally friendly or green extraction processes are now being applied, one of which is microwave-assisted extraction.Based on research results, it is known that microwave pectin extraction has a higher yield and shorter extraction time compared to conventional methods. The best extraction results were obtained at a power of 540 Watts, with an optimal extraction time of 11 minutes and a solvent ratio of 1:20, with the highest yields being 7.53%, 7.11%, and 6.48%, respectively. The objectives of this study were (i) to determine the best microwave power in the extraction process, (ii) to determine the optimal extraction time, and (iii) to determine the best solvent ratio in the extraction process.